Liturgical building blocks in medieval women's writing; data resulting from “Women Making Memories: Liturgy and the Remembering Female Body in Medieval Holy Women’s Texts” - Perk, G G; Perk, G G (University of Oxford, 2023)
WMM explores medieval women writers' strategical use of liturgical memory arts. Close-reading of 6 texts by medieval women as well as of liturgical texts is central to the project. When doing so, memorial building blocks are identified. The data consists of brief English paraphrases of relevant passages from these texts in different medieval vernaculars. Each paraphrase is identified as a particular building block. This dataset results from “Women Making Memories: Liturgy and the Remembering Female Body in Medieval Holy Women’s Texts,” Godelinde Gertrude Perk’s MSCA-IF project at the Faculty of Medieval and Modern Languages at the University of Oxford. This project has received funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement No 842443.